Load-resisting mechanism to mitigate progressive collapse of flat slab structures - Li, Bing (2015)
For reinforced concrete flat slab structures, column failure due to unexpected extreme loading may significantly increase the moment and shear force at adjacent slab–column connections, which can trigger punching shear failure at these connections and result in progressive collapse of flat slab structures. To determine the possible load-resisting mechanisms developed in flat slab structures in resisting progressive collapse, three multi-panel flat slab substructures are tested in this study. A flat slab substructure is tested as a control specimen. The remaining two specimens are strengthened by adding drop panels or post-installed shear bolts. Punching shear failure is observed in the control specimen and the specimen with post-installed shear bolts after reaching their yield loads. However, even the control specimen without any strengthening exhibited considerable post-failure resistance and deformation capacity mainly due to sufficient integrity reinforcement, which had been installed in the bottom of the slab. Test results indicated that drop panels not only increase the flexural resistance but also raise the punching shear resistance of the connections significantly. Thus, no obvious punching shear failure is observed in the specimen with drop panels. However, post-installed shear bolts can only increase the punching shear resistance. For post-failure behaviour, this is not very effective. The test results demonstrated that flexural failure dominates the performance of test specimens, as relatively low slab reinforcement ratio but high span/thickness ratio was designed.